2007
DOI: 10.1158/1078-0432.ccr-06-1807
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensitization of Cancer In vitro and In vivo by Nitric Oxide Signaling

Abstract: Purpose: Hypoxia contributes to drug resistance in solid cancers, and studies have revealed that low concentrations of nitric oxide (NO) mimetics attenuate hypoxia-induced drug resistance in tumor cells in vitro. Classic NO signaling involves activation of soluble guanylyl cyclase, generation of cyclic GMP (cGMP), and activation of cGMP-dependent protein kinase. Here, we determined whether chemosensitization by NO mimetics requires cGMP-dependent signaling and whether low concentrations of NO mimetics can chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(90 citation statements)
references
References 35 publications
7
81
0
2
Order By: Relevance
“…Hypoxia contributes to malignant progression in cancer through the stimulation of tumor cell phenotypes that include increased invasive and metastatic potential, as well as resistance to radiation and chemotherapy (5)(6)(7)(8). Because these are survival traits selected by hypoxia, it is also possible that exposure to low levels of oxygen leads to adaptive responses that allow tumor cells to escape from immune surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia contributes to malignant progression in cancer through the stimulation of tumor cell phenotypes that include increased invasive and metastatic potential, as well as resistance to radiation and chemotherapy (5)(6)(7)(8). Because these are survival traits selected by hypoxia, it is also possible that exposure to low levels of oxygen leads to adaptive responses that allow tumor cells to escape from immune surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized phase 2 trial, a combination of GTN plus vinorelbine and cisplatin was shown to improve the response rate and time to progression in comparison with vinorelbine and cisplatin alone in previously untreated patients with stage IIIB/IV NSCLC (38). Furthermore, the NO-cGMP signaling pathway has been reported to have a strong association with NO-induced attenuation of chemoresistance under hypoxic conditions (30). It is noteworthy that this attenuation was not found under normoxic conditions (31).…”
Section: Discussionmentioning
confidence: 99%
“…Activated p53 in tumor tissues promotes the apoptosis of cancer cells by p53-dependent anticancer agents, including cisplatin and vinorelbine (16). Furthermore, NO-mimetics have been reported to attenuate hypoxia-induced drug resistance via cyclic guanosine monophosphate (cGMP)-dependent signaling (30). NO donors may be a promising novel therapy in combination with anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…De même, combiné à l'oxaliplatine, le NCX-4040 a montré, in vivo, une activité antitumorale contre les tumeurs coliques humaines résistantes ou non à la doxorubicine 3 [36]. Enfin, la trinitrine, ou glycéryl trinitrate (GTN), un autre donneur de NO, sensibilise, in vivo, à la doxorubicine les tumeurs de la prostate humaine [37].…”
Section: éTudes Précliniquesunclassified